Effects of low-intensity home-based exercise on cognition in older persons with mild cognitive impairment: a direct comparison of aerobic versus resistance exercises using a randomized controlled trial design - Krootnark, Kitsana; Chaikeeree, Nithinun; Saengsirisuwan, Vitoon; Boonsinsukh, Rumpa (Frontiers in Medicine, 2024)
Background: It has been reported that both aerobic exercise and resistance exercise can improve cognitive function in older people with mild cognitive impairment (MCI), but it is unclear which type of exercise has a higher impact on cognitive function. Additionally, low-intensity exercise is considered safe for the elderly and can be done at home. This study aimed to compare the effects of 3-month low-intensity home-based exercises, aerobic versus resistance exercises, on cognitive function in people with MCI.This study was a single-blind randomized controlled trial conducted in a suburban community. Ninety eligible participants aged 60-80 years were randomly assigned into aerobic exercise, resistance exercise or control group (30 in each group). The aerobic and resistance exercise groups underwent 3 months of low-intensity exercise at home (35 minutes/day, 5 days/week). The control group performed their usual daily activities. The Montreal Cognitive Assessment Thai version (MoCA), Trail Making Test Part A and B (TMT-A, TMT-B), Stroop Color and Word Test (SCWT), forward and backward Digit Span Test (DST-F, DST-B) and Stick Design Test (SDT) were administered before training, 3-month after training and 3-month follow-up.Results: All participants completed a 3-month exercise program, but during the follow-up, data were gathered from 28, 27 and 26 participants in the aerobic, resistance, and control groups, respectively. Both aerobic and resistance groups showed significant improvements in all outcome measures during posttraining and follow-up, except SDT, while there was no cognitive improvement in control group at posttraining and follow-up. Compared to those in the control group, the aerobic group had significant improvements in MoCA, TMT-A, TMT-B and SCWT, while resistance group had significant improvements in MoCA and TMT-B at posttraining and follow-up. There were no differences in any outcome measures between aerobic and resistance groups, except SCWT, which was significantly greater in the aerobic group than in the resistance group posttraining.Low-intensity exercise, whether aerobic or resistance training, was effective at improving cognitive function in older people with MCI, and the effects were sustained at the 3-month follow-up.